Estimating phase with a random generator: strategies and resources in multiparameter quantum metrology - Yousefjani, Rozhin; Nichols, Rosanna; Salimi, Shahriar; Adesso, Gerardo (American Physical Society, 2017)
Quantum metrology aims to exploit quantum phenomena to overcome classical limitations in the estimation of relevant parameters. We consider a probe undergoing a phase shift φ whose generator is randomly sampled according to a distribution with unknown concentration κ, which introduces a physical source of noise. We then investigate strategies for the joint estimation of the two parameters φ and κ given a finite number N of interactions with the phase imprinting channel. We consider both single qubit and multipartite entangled probes, and identify regions of the parameters where simultaneous estimation is advantageous, resulting in up to a twofold reduction in resources. Quantum enhanced precision is achievable at moderate N, while for sufficiently large N classical strategies take over and the precision follows the standard quantum limit. We show that full-scale entanglement is not needed to reach such an enhancement, as efficient strategies using significantly fewer qubits in a scheme interpolating between the conventional sequential and parallel metrological schemes yield the same effective performance. These results may have relevant applications in optimization of sensing technologies.